Efficient and stable perovskite solar cells thanks to dual functions of oleyl amine-coated PbSO4(PbO)4 quantum dots: Defect passivation and moisture/oxygen blocking. (February 2020) - Chen, Chong; Li, Fumin; Zhu, Liangxin; Shen, Zhitao; Weng, Yujuan; Lou, Qiang; Tan, Furui; Yue, Gentian; Huang, Qingsong; Wang, Mingtai
Abstract: The defects in perovskite crystals and the penetration of moisture/oxygen into the perovskite layer are major problems for perovskite solar cells (PSCs) to achieve long-term stability and high power conversion efficiency (PCE). However, there is still a lack of multifunctional passivation materials to solve these problems. Herein, for the first time, we report oleyl amine-coated PbSO4 (PbO)4 quantum-dots (QDs), as a passivation material with dual functions to simultaneously passivate the surface defects and block the penetration of moisture/oxygen into the perovskite layer for stable and efficient PSCs. The PbSO4 (PbO)4 QDs significantly reduce the defect density of the as-prepared CH3 NH3 PbI3 films by passivating under-coordinated Pb ions and I anions and effectively enhance charge extraction efficiency at the TiO2 /CH3 NH3 PbI3 and CH3 NH3 PbI3 /spiro-OMeTAD interfaces. Moreover, the hydrogen bond between H atoms of the OA and I atoms of the perovskite and the interface electric field at CH3 NH3 PbI3 /OA interface also contribute to the improvement of efficiency and stability of PSCs. Finally, higher PCE (20.02%) is achieved by the PSCs with OA-coated PbSO4 (PbO)4 QDs compared to that (16.86%) of the PSCs without OA-coated PbSO4 (PbO)4, corresponding to a 18.7% enhancement. Moreover, the PSCs with OA-coated PbSO4 (PbO)4 QDs maintain 90% of initial efficiency after operation for 280 h, indicating better stability than the PSCs without PbSO4 (PbO)4 QDs. Graphical abstract: Device structure and charge separation diagram. Image 1 Highlights: Oleyl amine (OA) coated-PbSO4 (PbO)4 quantum-dots are synthesized. PbSO4 (PbO)4 QDs passivate defect states in perovskite crystals. OA results in an interfacial electric field for charge extraction. The efficiency and stability of the PSCs are significantly improved.